2003
DOI: 10.1007/s10067-003-0812-4
|View full text |Cite
|
Sign up to set email alerts
|

The autonomic nervous system in systemic sclerosis. A review

Abstract: The autonomic nervous system is an underestimated target of systemic sclerosis alterations. In this review we analyzed the major manifestations of its involvement, reconsidering the main theories of its pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
0
18
0
3
Order By: Relevance
“…Nevertheless, pSS has also been shown to affect multiple nonexocrine organs such as the nervous system and the gastrointestinal (GI) tract. Studies have found signs of autonomic nervous dysfunction (AD) in pSS 1,2 , reminiscent of what has also been reported in other autoimmune diseases such as inflammatory bowel disease 3,4,5,6 , rheumatoid arthritis 7 , systemic sclerosis (SSc) 8 , and systemic lupus erythematosus 9 . Various GI symptoms such as dysphagia, symptoms of gastroparesis, and irritable bowel syndrome (IBS) have been reported to be more common in patients with pSS than in the general pop-ulation 10,11,12 .…”
mentioning
confidence: 95%
“…Nevertheless, pSS has also been shown to affect multiple nonexocrine organs such as the nervous system and the gastrointestinal (GI) tract. Studies have found signs of autonomic nervous dysfunction (AD) in pSS 1,2 , reminiscent of what has also been reported in other autoimmune diseases such as inflammatory bowel disease 3,4,5,6 , rheumatoid arthritis 7 , systemic sclerosis (SSc) 8 , and systemic lupus erythematosus 9 . Various GI symptoms such as dysphagia, symptoms of gastroparesis, and irritable bowel syndrome (IBS) have been reported to be more common in patients with pSS than in the general pop-ulation 10,11,12 .…”
mentioning
confidence: 95%
“…It has been hypothesized that microcircle vasculopathy and autonomic nervous system alterations, commonly observed in SSc, are the cause of atrophy of the smooth muscle cells and of the fibrosis that leads to gastric dysmotility [39][40][41][42]. In this regard, an ultrastructural study of the gastric wall showed alterations in the axoplasma of the nerve fibres (reduction of the neurotubules and of the neurofilaments, swelling of the mitochondria, lipofuscin deposits) and accumulation of elastic fibres and collagen around the nerve endings, which separate them from the smooth muscle cells [43].…”
Section: Discussionmentioning
confidence: 99%
“…The association of higher plasma leu-enkephalin levels with loss of digital pulp in SSc patients supports their potential relevance in subsequent tissue remodeling from increased fibrogenic activity. Reported physiologic interactions of cytokines such as transforming growth factor-beta expression and opioid agonists possibly contribute to wound healing (18). Indirectly, lower met-enkephalin levels have been demonstrated to promote apoptosis via the cellular caspase-3 pathway in cultured cells (7).…”
Section: Discussionmentioning
confidence: 99%